Sandworms of Dune [compact disc, unabridged] - Herbert, Brian (Audio Renaissance, 2007)
Building on the events of Frank Herbert's final novel, Chapterhouse of Dune, a ship of escaped refugees uses genetic technology to revive talented figures from the world's past in order to safeguard their survival.